The main determinants of banking crises in OECD countries - Pedro, C. P.; Ramalho, J. J. S.; Silva, J. V. (Review of World Economics, 2018)
Banks’ stability can be affected by economic fluctuations, banks’ risk-taking behavior, connections among banks and countries’ financial system structure. At the same time, banking regulation and supervision were designed to protect banks from failure, but a large number of banking crises were not prevented recently. Using binary response models for panel data and focusing on OECD countries, this paper studies the main determinants of banking crises over a period of 21 years. Results suggest a bank’s high debt and a country’s low GDP growth rate as the major determinants of banking crises. There is also evidence of contagion across countries from the same geographical region and from G7 to other countries, and that bank-based financial systems are less prone to borderline banking crises. Regulatory and supervision practices are found not to have been relevant in bankruptcy prevention.